Optimizing thiopurine therapy in children with acute lymphoblastic leukemia: A promising “MINT” sequencing strategy and therapeutic “DNA-TG” monitoring - Guo, Hong-Li; Zhao, Yue-Tao; Wang, Wei-Jun; Dong, Na; Hu, Ya-Hui; Zhang, Yuan-Yuan; Chen, Feng; Zhou, Li; Li, Tao (Frontiers in Pharmacology, 2022)
Thiopurines, including thioguanine (TG), 6-mercaptopurine (6-MP) and azathioprine (AZA), are extensively used in clinical practice in children with acute lymphoblastic leukemia (ALL) and inflammatory bowel disease. However, the common adverse effects caused by myelosuppression and hepatotoxicity limit their application. Metabolizing enzymes such as thiopurine S-methyltransferase (TPMT), Nudix hydrolase 15 (NUDT15), inosine triphosphate pyrophosphohydrolase (ITPA), and drug transporters like multidrug resistance-associated protein 4 (MRP4) have been reported to mediate the metabolism and transportation of thiopurine drugs. Hence, the single nucleotide polymorphisms (SNPs) in those genes could theoretically affect the pharmacokinetics and pharmacological effects of these drugs, and might also become one of the determinants of the clinical efficacy and adverse effects. Moreover, long-term clinical practices have confirmed that thiopurine-related adverse reactions are associated with the systemic concentrations of their active metabolites. In this review, we mainly summarized the pharmacogenetic studies on thiopurine drugs. We also evaluated the therapeutic drug monitoring (TDM) researches and focused on those active metabolites, hoping to continuously improve monitoring strategies for thiopurines therapy to maximize therapeutic efficacy and minimize adverse effects or toxicity. We proposed that tailoring thiopurines dosing based on MRP4, ITPA, NUDT15, and TMPT genotype, defined as “MINT” panel sequencing strategy, might contribute towards improving the efficacy and safety of thiopurines. Moreover, the DNA-incorporated thioguanine nucleotides (DNA-TG) metabolite level was more suitable for red cell 6-thioguanine nucleotides (6-TGNs) monitoring, which can better predict the efficacy and safety of thiopurines. Integrating the panel “MINT” sequencing strategy with therapeutic “DNA-TG” monitoring would offer a new insight into the precision thiopurines therapy for pediatric ALL patients.